Polymeric Carriers for Biomedical and Nanomedicine Application - Lima, Sofia; Reis, Salette (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book focuses on the design of polymeric delivery systems for biomedical and nanomedicine applications as well as on understanding how such biomaterials interact in the physiological environment. The reader will find an encompassing view on the state-of-the-art of polymeric carriers, showing how current research deals with new stimuli-responsive systems for cancer therapies and biomedical challenges, namely overcoming the skin barrier. The published papers cover topics ranging from novel production methods and insights on hybrid polymers to applications as diverse as nanoparticles, hydrogels and microneedles for antifungal skin therapy, peptide and siRNA delivery, enhanced skin absorption of bioactive molecules, and anticancer therapy. The book comprises one review paper and nine research papers.